Calibrating annual sedimentation in a glacial lake Lake Linné, Svalbard, Norway - Snyder, Sydney (2012)
This study will focus on the most recent depositional year, fall 2010 through summer 2011. The study is a continuation of previous projects and investigates modern sedimentation in Lake Linné in order to formulate a relationship between sedimentation and environmental climate variables. Not only was the amount of total accumulated sediment anomalously low during last season, but the proportions of sediment attributed to fall deposition and the spring melt season were unconventional. Sediment varves from the most recent atypical depositional year have the potential to complicate the extensive varve record. Misinterpretations of seasonal varves may therefore convolute the record of past environmental conditions, thus a clear understanding of this contemporary record is essential to correctly interpreting past High Arctic climate conditions. The National Science Foundation, The Svalbard REU, The Cascade Mentoring Program - Mt. Holyoke College